The contribution of wind-wave energy at sea bottom to the modelling of rhodolith beds distribution in an off-shore continental shelf - AGNESI, SABRINA; ANNUNZIATELLIS, ALDO; INGHILESI, ROBERTO; MΟ, GIULIA; ORASI, ARIANNA (Mediterranean Marine Science, 2020)
The study aims to investigate the relationship between the presence of rhodolith beds and the effect on the shelf bottom boundary layer due to the action of surface wind waves. The study area is situated off-shore and north-west of Elba Island in the Western Mediterranean Sea, an area known to be characterized by rhodolith beds. A binomial logistic regression model is used in order to analyse the relationship between wind-wave energy at sea bottom, bathymetry and rhodolith bed occurrence. The results indicate a positive correlation between rhodolith bed occurrence and wave energy, while the relation with bathymetry is weaker in all the trials. The wave energy confidence interval associated to the rhodolith bed probability is also estimated, thereby informing on wind wave energy values required for the modelling of this particular benthic habitat in off-shore shelf areas.